Activity Based Costing (ABC) on Company Performance with Competitive Advantage as A Variable Mediation - Putri, Annadia; Bastian, Elvin; Fitriyani, Fara (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to examine the effect of Activity Based Costing (ABC) on Company Performance with CompetitiveAdvantage as a Mediation variable. This research is a type of quantitative research, data collected using primary dataand questionnaires to obtain information for respondents, namely Middle Managers who work at ManufacturingCompanies located in Banten Province in Serang and Cilegon Regencies. The analytical method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) Path Modeling with SmartPLS 3.0 analysis tool. The results of this study are 1) Activity Based Costing has a positive and significant effect on company performance. 2) Activity Based Costing has a positive and significant effect on Competitive Advantage. 3) Competitive advantage has apositive and significant effect on Company Performance